JOINT REPLENISHMENT AND JOINT DELIVERY OF MULTIPLE ITEMS - Shafiq, Muhammad; Luong, Huynh Trung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
In his paper, joint replenishment and joint delivery coordination mechanism is developed using integers multiple technique to coordinate replenishments and deliveries of multiple items in a supply chain comprising multiple firms at each level. The proposed coordination mechanism allows different replenishment and delivery cycle times for the firms located at same level of the supply chain. The basic replenishment cycle time of each warehouse is defined to be an integer multiple of basic delivery cycle time which helps coordinating replenishments and deliveries. The proposed model is then extended using integer powers of two multiple coordination technique. The practical implementation and implications of the proposed models have been shown through numerical experiments. Sensitivity analyses are also conducted to find out the impact of various input parameters. Moreover, it is found that the proposed integers multiple coordination mechanism outperforms the typical integer powers of two multiple mechanism in specific scenarios.